Adults with Loeys-Dietz syndrome and vascular Ehlers-Danlos syndrome: a cross-sectional study of patient experiences with physical activity. Issue 10 (8th May 2022) - Johansen, Heidi; Velvin, Gry; Lidal, Ingeborg
Abstract: Purpose: To study patient experiences with physical activity among persons with Loeys-Dietz- or vascular Ehlers-Danlos syndrome. Materials and methods: A postal questionnaire survey in 2018. Seventy adults with molecularly verified Loeys-Dietz syndrome types 1-4, or vascular Ehlers-Danlos syndrome recruited through a National Resource Centre for Rare Disorders in Norway. Results: The response rate was 74%, (Loeys-Dietz n = 34, vascular Ehlers-Danlos n = 18), aged 18 to 68 years, 58% women. In total, 88.5% reported they had received advice regarding physical activity and most (77%) had modified their habits. Fifty percent had an appropriate- and 40% a low mean physical activity sum score. Another 10% had too high physical activity levels due to high intensity scores. Lower scores with the Fatigue Severity Scale ( p = 0.033) and the anxiety subscale of the Hospital Anxiety and Depression Scale ( p = 0.021), were associated with high physical activity levels. About a third reported unmet rehabilitation needs. Conclusion: Many adults with Loeys-Dietz- or vascular Ehlers-Danlos syndrome may have a potential to reach more favorable physical activity levels by increasing the frequency and duration of activities. Future directions should include evaluation of effects of professional-led practical and safe physical activity sessions as well as customized multidisciplinary rehabilitation programs for these patient groups.